Islamic Boarding School at University: A Strong Pathway for Integrating Religion and Science - Iffat Maimunah; Miftahul Huda; Arina Haque; Zubaidah Zubaidah (J-PAI: Jurnal Pendidikan Agama Islam, 2021)
This paper aims to explain the implementation of the establishment of ma'had al-jami'ah UIN Maulana Malik Ibrahim Malang as a form of implementing the integration of higher education and Islamic boarding schools. This paper uses a descriptive-analytical approach. The technique used by researchers in collecting data is through library data and field observations. This paper complements the shortcomings of previous studies, the previous studies examine the integration of pesantren (boarding school) and university in 3 models; first, a study on the trend of pesantren establishing a university to increase religious knowledge called ma'had 'aly. Second, the Islamic boarding school, an attempt by pesantren to establish a university in the pesantren environment. The third, the efforts of university (PTKIN) are philosophically and conceptually concerned in the integration of science and religion which are implemented in the integration between university and pesantren. This study explains practically the development of the integration of Islamic higher education and pesantren/ma'had as a model of formal institutions capable of realizing the needs of newer system education. Development of the integration between Islamic Universities and Islamic boarding schools which produces superior scholars, mastering science, and technology (IPTEK) but it should not ignore the aspects of faith and piety (IMTAQ).